Annunciations (Open Book Publishers, 2021)
"Our contemporary culture is communicating ever-increasingly through the visual, through film, and through music. This makes it ever more urgent for theologians to explore the resources of art for enriching our understanding and experience of the Judeo-Christian tradition. Annunciations: Sacred Music for the twenty-First Century, edited by George Corbett, answers this need, evaluating the relationship between the sacred and the composition, performance, and appreciation of music.